2019
DOI: 10.1101/532317
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Visual imagery and visual perception induce similar changes in occipital slow waves of sleep

Abstract: Previous studies have shown that regional slow wave activity (SWA) during NREM-sleep is modulated by prior experience and learning. While this effect has been convincingly demonstrated for the sensorimotor domain, attempts to extend these findings to the visual system have provided mixed results. Here we asked whether depriving subjects of external visual stimuli during daytime would lead to regional changes in slow waves during sleep and whether the degree of 'internal visual stimulation' (spontaneous imagery… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
3
2

Relationship

4
1

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 79 publications
0
8
0
Order By: Relevance
“…Because wake data were not available for the above subjects, specific analyses aimed at comparing sleep-and wake-related brain activity (see below) were performed in a different sample of 12 healthy adult individuals (age 25.5 Ϯ 3.7, 6 females) who underwent overnight hd-EEG sleep recordings after having spent 8 h in the sleep laboratory while watching movies (analyses of wake and NREM sleep data from these subjects has been reported previously (Bernardi et al, 2019). These recordings were performed at the Lausanne University Hospital under a research protocol approved by the local ethical committee.…”
Section: Methodsmentioning
confidence: 99%
“…Because wake data were not available for the above subjects, specific analyses aimed at comparing sleep-and wake-related brain activity (see below) were performed in a different sample of 12 healthy adult individuals (age 25.5 Ϯ 3.7, 6 females) who underwent overnight hd-EEG sleep recordings after having spent 8 h in the sleep laboratory while watching movies (analyses of wake and NREM sleep data from these subjects has been reported previously (Bernardi et al, 2019). These recordings were performed at the Lausanne University Hospital under a research protocol approved by the local ethical committee.…”
Section: Methodsmentioning
confidence: 99%
“…Tables 1 and 2 report demographic and clinical characteristics for all patients. An additional control group of 24 healthy adult volunteers (i.e., HSs; age range, 20–47 years; 13 females) was studied with the same hd-EEG recording system at the Lausanne University Hospital (Lausanne, Switzerland; analyses of NREM sleep data from these subjects, not involving the study of inter-hemispheric slow-wave propagation, have been reported in previous work; Siclari et al, 2018 ; Bernardi et al, 2019a , b ). Before their inclusion in the study, HS group individuals underwent a clinical interview to exclude a history of sleep, medical, and psychiatric disorders.…”
Section: Methodsmentioning
confidence: 99%
“…Indeed, seminal work in rats demonstrated that locally synchronized neuronal off-periods similar to those underlying the generation of sleep slow waves (0.5-4 Hz) occur more frequently as a function of time spent awake (Vyazovskiy et al, 2011). Studies in humans also revealed that such increases are of greater magnitude in brain areas that are more intensively 'used' during the waking period (Hung et al, 2013;Quercia et al, 2018;Bernardi et al, 2019;Petit et al, 2019). Interestingly, the occurrence of sleep-like events in brain areas related to the execution of ongoing activities has been shown to potentially determine temporary behavioral impairments in a variety of different tasks, including impulse control, visuo-motor coordination and stimulus categorization (Bernardi et al, 2015;Nir et al, 2017).…”
Section: Neural Correlates Of Emotion Suppression Failuresmentioning
confidence: 99%